2006
DOI: 10.1016/j.chembiol.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes Intermediates Do the Job!

Abstract: The SARS coronavirus main proteinase is a prime target for antiviral therapy. In this issue of Chemistry & Biology, Wu et al. describe potent inhibition of the enzyme by benzotriazole esters, which were originally obtained as intermediates in the synthesis of lopinavir derivatives .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…In addition, a number of non‐peptidic, reversible inhibitors of the main protease have been discovered by virtual screening and/or docking on the basis of the crystal structure; examples for such compounds are cinanserin , arylboronic acids , isatin derivatives , selected diarylsulfones and a variety of others . Other non‐peptidic inhibitors, such as benzotriazole esters and non‐warheaded benzo triazoles , were discovered by screening of chemical libraries and subsequent optimization of the hits by medicinal chemistry. Chloropyridyl esters have been derived from the benzotriazole esters and found to have good antiviral activity in cell culture .…”
Section: Discovery and Design Of Mpro Inhibitorsmentioning
confidence: 99%
“…In addition, a number of non‐peptidic, reversible inhibitors of the main protease have been discovered by virtual screening and/or docking on the basis of the crystal structure; examples for such compounds are cinanserin , arylboronic acids , isatin derivatives , selected diarylsulfones and a variety of others . Other non‐peptidic inhibitors, such as benzotriazole esters and non‐warheaded benzo triazoles , were discovered by screening of chemical libraries and subsequent optimization of the hits by medicinal chemistry. Chloropyridyl esters have been derived from the benzotriazole esters and found to have good antiviral activity in cell culture .…”
Section: Discovery and Design Of Mpro Inhibitorsmentioning
confidence: 99%
“…Left with few other options, physicians also tested HIV proteinase inhibitors (Stockman et al, 2006), and Wu et al (2006) found that one of them, lopinavir, targeted SARS-CoV M pro with an IC 50 of z50 mM. In their search for derivatives of lopinavir with an improved inhibitory action toward M pro , Wu et al (2006) noticed by serendipity that the intermediate benzotriazole esters occurring during the synthesis of these derivatives were better inhibitors of the enzyme than the final products (see also Hilgenfeld and Pumpor, 2006). These benzotriazole esters are the result of the activation of carboxylic acids by 2-(1H-benzotriazole-1-yl)-1,1,3,3-tetramethyluronium hexafluorophosphate (HBTU), which was used as a coupling reagent in the synthesis of the lopinavir-like molecules.…”
Section: Introductionmentioning
confidence: 99%
“…The transition between the two conformations is believed to depend on the protonation/deprotonation of a histidine residue (His163) that interacts with the P1 glutamine residue of the substrate; this has been reproduced using molecular dynamics simulations [69 ]. Several structures of complexes with peptidomimetic inhibitors have been determined for the enzyme [66,71 ,72,73] and compounds that acylate the active site cysteine residue were also described as potent inhibitors [74,75]. Peptidyl aldehydes have been designed and synthesized as potentially reversible inhibitors [76].…”
Section: Replication: Nucleic Acid and Protein Synthesismentioning
confidence: 99%